2008
DOI: 10.1523/jneurosci.5187-07.2008
|View full text |Cite
|
Sign up to set email alerts
|

Disruption of Krox20-Nab Interaction in the Mouse Leads to Peripheral Neuropathy with Biphasic Evolution

Abstract: Krox20/Egr2 is a zinc finger transcription factor that plays essential roles in several developmental processes, including peripheral nervous system myelination by Schwann cells, where it acts as a master gene regulator. Krox20 is known to interact with cofactors of the Nab family and a mutation affecting isoleucine 268, which prevents this interaction, has been shown to result in congenital hypomyelinating neuropathy in humans. To further investigate the role of this interaction, we have introduced such a mut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
31
0

Year Published

2008
2008
2012
2012

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(35 citation statements)
references
References 54 publications
4
31
0
Order By: Relevance
“…Several independent studies have shown Egr2 in conjunction with Nab expression is critical for peripheral myelination (Le et al, 2005b; Desmazieres et al, 2008; Baloh et al, 2009). Thus, knockout mice with hypomyelination phenotype (e.g.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Several independent studies have shown Egr2 in conjunction with Nab expression is critical for peripheral myelination (Le et al, 2005b; Desmazieres et al, 2008; Baloh et al, 2009). Thus, knockout mice with hypomyelination phenotype (e.g.…”
Section: Resultsmentioning
confidence: 99%
“…Although the association of Chd4 with NAB coregulators provided the mechanistic basis for this study, the resulting phenotype is significantly less severe than that caused by deletion of both NAB genes, or by knock-in of a NAB-resistant allele of Egr2 (Le et al, 2005b; Desmazieres et al, 2008; Baloh et al, 2009). One possible explanation could be redundancy with Chd3.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Interestingly, Egr1 has previously been shown to bind to cognate sites within the human Socs1 promoter and to positively regulate Socs1 expression in macrophages [37]. As one of the binding sites is conserved in the murine promoter, it is possible that Egr2 is able to bind to the Socs1 promoter directly and repress its activity, perhaps in combination with a member of the cofactor family of Nab proteins (for example, see [38]). However, it is likely that regulation is complex, potentially depending on interplay with other transcription factors such as the established Egr2 repressor Gfi-1B [39], as the effects of Egr2 manipulation on Socs1 expression, as shown in Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Alkaline phosphatase activity was revealed using the NBT/ or INT/BCIP substrates (Roche). Mouse immunolabelling was performed using rabbit anti-Krox20 (Desmazières et al, 2008) and rat anti-GFP (Nacalai Tesque) antibodies. For double labelling, in situ hybridization was performed as above and rat anti-HA antibody (Roche) was added with the anti-DIG antibody.…”
Section: In Situ Hybridization Immunolabelling and X-gal Stainingmentioning
confidence: 99%